Feasibility of using his bundle pacing with boston scientific generators. (14th October 2021) - Mark, N; Papageorgiou, N; Ramplin, J; Monkhouse, C; Moore, P; Chow, A; Hunter, R; Sporton, S; Providencia, R; Earley, M; Elliott, J; Muthumala, A
Abstract: Introduction: His bundle pacing (HBP) aims to deliver physiological activation of the ventricles via the native His-Purkinje conduction system. A challenge of HBP is the limited market of implantation tools, pacing leads and specifically designed pacing algorithms. Purpose: Over the last three years both Medtronic (MDT) and Boston Scientific (BSC) generators have been used for HBP in a large tertiary centre. We examined whether there was any difference between lead parameters and battery longevity depending on the type of manufacturer used. Methods: Patients implanted with a MDT Select Secure model 3830 lead were included in this retrospective study. Data collected included HBP thresholds (analysed at 1ms pulse width) at implant and at the most recent device check, HBP percentages and battery longevity (months). Battery longevity were calculated by adding duration of follow up and estimated battery life at last follow up. Results: A total of 31 patients were included for data analysis (58% male and mean age 72 years). 18 patients had MDT generators of which 3 were PPMs, 5 were CRT-Ps and 10 were CRT-Ds. 13 patients had BSC generators of which 5 were PPMs, 5 were CRT-Ps and 3 were CRT-Ds. Mean follow up of the cohort was 12.7±9.02 months. Mean HBP percentages were 77±37% and 72.2±42.1% for MDT and BSC, respectively (p=0.430). Mean HBP threshold (Volts) at implant was significantly lower with BSC vs MDT (0.85±0.58 vs 1.84±1.06, p=0.01), and similar after follow up (1.01±0.91 vs 1.32±0.73, p=NS). There were no statistically significant differences between mean HBP threshold at implant compared to follow up for both manufacturers. Interestingly, mean battery longevity for BSC vs MDT generators was significantly higher (136±29.3 vs 90.5±29.1, p<0.001). Longevity was also compared for PPM/CRT-P and CRT-D separately. For PPM/CRT-P, BSC generators had significantly higher longevity as compared to MDT (141.6±33.1 vs 91.6±34.5, p=0.009). This difference was not observed for CRT-Ds between the 2 manufacturers (p=0.068). Conclusion: Our results suggest HBP with MDT Select Secure 3830 lead is feasible with BSC generators. There is potentially greater battery longevity with BSC compared to MDT generators. Further studies are needed with greater numbers and longer follow up to confirm this finding. Funding Acknowledgement: Type of funding sources: None.